FARSITE: Federated, available, and reliable storage for an incompletely trusted environment - Adya, Atul; Bolosky, Bill; Castro, Miguel; Chaiken, Ronnie; Cermak, Gerald; Douceur, John (JD); Howell, Jon; Lorch, Jay; Theimer, Marvin; Wattenhofer, Roger and (Proceedings of the 5th Symposium on Operating Systems Design and Implementation (OSDI), 2002)
Farsite is a secure, scalable file system that logically functions as a centralized file server but is physically distributed among a set of untrusted computers. Farsite provides file availability and reliability through randomized replicated storage; it ensures the secrecy of file contents with cryptographic techniques; it maintains the integrity of file and directory data with a Byzantine-fault-tolerant protocol; it is designed to be scalable by using a distributed hint mechanism and delegation certificates for pathname translations; and it achieves good performance by locally caching file data, lazily propagating file updates, and varying the duration and granularity of content leases. We report on the design of Farsite and the lessons we have learned by implementing much of that design.